(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Religions on the film set: articles 403-404 of the Criminal Code in the plots of the screenplay Religions are often protagonists on the big screen. The roles they play vary according to the centrality of the religious element in the script. From films that represent a phenomenology of the sacred to those in which the element of faith is only an appearance, the connection between cinema and religions is close. This relationship can raise legal problems when the script offends a religious denomination by vilifying people or things. In this case the freedom of artistic expression of the filmmaker can conflict with the protection of the religious denomination and the religious sentiment of the viewer. The judges are called to balance these freedoms of equal constitutional level in order to transform the antagonism sometimes present on the film set into co-protagonism. SOMMARIO: 1. Le religioni attrici sui grandi schermi - 2. Blasfemia cinematografica: quando il cineasta offende il sentimento religioso dello spettatore - 3. La censura alla regia: il reato di vilipendio della religione dello Stato nella settima arte - 4. Giudici in platea tra pluralismo confessionale e libertà di espressione artistica - 5. L’art. 19 Cost. e l’art. 33 Cost. in scena: da antagonisti a coprotagonisti.